Real-time Reverse Transcription PCR-based SARS-CoV-2 Detection in Khwaja Yunus Ali Medical College Hospital, Enayetpur, Sirajganj, Bangladesh (KYAMC Journal, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a global pandemic declared on 11 March 2020 by World Health Organization (WHO). It is a highly pathogenic viral infection caused by SARS-CoV-2 which has caused global health concern. The emergence of SARS-CoV-2 infection has triggered a global need for accurate diagnostic assays. Detection of viral RNA in clinical specimens is the hallmark of diagnosis.Objectives: The aim of present study was to determine the prevalence of SARS-CoV-2 infection in some districts of North Bengal area of Bangladesh according to age, sex and area distribution.Materials and Methods: This cross sectional descriptive study was carried out in the Department of Laboratory Services, KYAMCH, Enayetpur, Sirajganj, Bangladesh. Real-Time reverse transcription Polymerase chain reaction assay was used for detection of virus.Results: A total of 1760 cases in the month from March to May 2021 were tested, among which 310 (17.6%) cases were detected positive for SARS-CoV-2. Out of 310 positive cases 211 (68.06%) were male and 99 (31.94%) were female. Maximum positive cases were from Sirajganj followed by Pabna, Natore, Naogaon, Bogura, Gaibandha districts and some parts of Rajshahi district respectively.Conclusion: This is the first study for genetic detection of SARS-CoV-2 done in KYAMCH, Enayetpur, Sirajganj. Strategies of using rRT-PCR for detection of SARS-CoV-2 may facilitate early and confirmatory diagnosis of COVID-19KYAMC Journal.2021;12(02): 59-65